Inter-Contact Routing for using Mobile Phone System - M.Malathy, Dr; J.Alin Mercybha, P; Jebasty Kiruba, J; Benisha, M (International Journal of Engineering and Technology, 2018)
Disaster management is the important filed in our world. It is based on communication between rescue-workers and trapped survivors in the disaster situation. In this paper, two main components are namely messaging system and self rescue system. Messaging system runs on rescue workers as-well-as trapped survivors. Self rescue system runs on trapped survivors. When the rescue workers enter into the spot for recovery works they will provide network continuously within certain distance and range.Â The head node collects all the necessary information about the nearby trapped survivors in their group. The rescue worker forwards the collected information of the trapped survivors to the command centre. The command centre finds the route between rescue workers in disaster region using AODV routing protocol.Â Â